2021
DOI: 10.1088/1361-6501/ac3b0b
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent fault diagnosis method for rolling bearings based on feature transfer with improved DenseNet and joint distribution adaptation

Abstract: Mechanical intelligent fault diagnosis is an important method to accurately identify the health status of mechanical equipment. Traditional fault diagnosis methods perform poorly in the diagnosis of rolling bearings under complex conditions. In this paper, a feature transfer learning model based on improved DenseNet and joint distribution adaptation (FT-IDJ) is proposed. With this model, we apply it to implement rolling bearing fault diagnosis. A lightweight DenseNet model is firstly proposed to extract the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…An et al 23 exploited self-learning transferable networks for mechanical fault diagnosis with unlabeled and unbalanced data. Similar research based on deep transfer diagnosis can be found in Wu et al 24 and Han et al 25 Qian et al 26 improved DenseNet and joint distribution adaptation for the transfer diagnosis. The core idea of the methods above is automatically learning the feature information of the two working conditions by using the deep learning model, and finally achieve the knowledge transfer by shortening the gap between the two working conditions.…”
Section: Introductionsupporting
confidence: 55%
“…An et al 23 exploited self-learning transferable networks for mechanical fault diagnosis with unlabeled and unbalanced data. Similar research based on deep transfer diagnosis can be found in Wu et al 24 and Han et al 25 Qian et al 26 improved DenseNet and joint distribution adaptation for the transfer diagnosis. The core idea of the methods above is automatically learning the feature information of the two working conditions by using the deep learning model, and finally achieve the knowledge transfer by shortening the gap between the two working conditions.…”
Section: Introductionsupporting
confidence: 55%
“…The main contributions of this paper are as follows: (1) The NGO algorithm is improved by introducing chaotic mapping and leader mutation selection strategy, and it is verified that CLNGO is superior to NGO in both convergence speed and convergence accuracy. (2) The CLNGO algorithm is used to select key parameters in FMD and MNAD, which makes it self-adaptive. Compared with VMD and EMD, FMD, this method can realize better separation of fault information and noise, and the proposed method is superior to MOMEDA and MCKD combined with envelope analysis in terms of fault feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…where X is the number of eagles, X i is the ith solution, N is the number of populations, m is the number of variables. The objective function value is calculated by Equation (2).…”
Section: Northern Goshawk Optimization Algorithm (Ngo)mentioning
confidence: 99%
See 1 more Smart Citation
“…As the rapid development of CNN, its classic network structures like AlexNet [25], VGG-Nets [26], GoogLeNet [27], ResNet [28], and DenseNet [29] have appeared successively. Although the architectures of CNN are getting more and more complex, their image processing capabilities are getting stronger and stronger.…”
Section: Inverse Design DL Approachmentioning
confidence: 99%